Usage of NEWS for prediction of mortality and in-hospital cardiac arrest rates in a Turkish university hospital - ARIKAN, HÜSEYİN; KARAKURT, SAİT; ERYÜKSEL, SEMİHA EMEL (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2018)
Background/aim: Early warning scores (EWS), widely used around the world but not yet in Turkey, are composed of physiological parameters designed to determine potentially worsening patients to perform necessary interventions in time. The aim is to determine the national EWS (NEWS) of the patients to assess the relation between this score and length of hospital stay (LOHS), transfer to the ICU, 24-h and 28-day mortality rates, and the frequency of in-hospital cardiac arrest (IHCA). Materials and methods: NEWS of all the patients in the internal medicine clinics were calculated via a point prevalence study. The LOHS, transfer to the ICU, rates of mortality in the 24-h and 28-day period, IHCA rate, and the period of the stay in the ICU parameters were determined. Results: Out of 104 patients, 84 of them had low scores (<5), while 20 had mid/high scores. In mid/high-score group (score>5), transfer to the ICU, IHCA rate, and mortality rates within 24 h and 28 days were significantly higher. Conclusion: In this, the first prospective study about EWS in Turkey, 24-h and 28-day mortality rates, transfer to the ICU, and IHCA frequency of the patients with mid/high NEWS were higher.
Keywords: National early warning score; cardiac arrest; intensive care unit; mortality; EARLY WARNING SCORE; INTENSIVE-CARE; CLINICAL DETERIORATION; ADMISSION; RISK; VALIDATION